A Pilot Study to Assess Diabetes Knowledge Among Diabetics - Mariyam Mubarak Ali, Ahamada Safna; Lakshmi Bhuvana, Gunamanikyam (Indian Journal of Pharmacy Practice)
Background: Urbanization and life style changes in developing countries lead to increase in the incidence and prevalence of diabetes. Diabetes is a chronic disease which affects both genders of all age groups. Glycemic level of diabetic patients if not maintained within the normal limits leads to micro and macro vascular complications. The effective management of glycemic level is based on the disease awareness level of the patients, as education is the best way to increase the awareness about a disease and to prevent worsening of the disease conditions. Aim: This descriptive study aims at assessing the diabetic knowledge among diabetic patients. Material and Methods: Patients aged 18-65 years of both genders diagnosed with diabetes admitted to the hospital were recruited and their knowledge about diabetes is obtained by using a questionnaire. Results: A total of 339 patients were recruited for the study out of which 48.08% were females and 51.91% were males. Majority of the study population (36.57%) were in the age group of 51-60 years. In our study, 64% of subjects belong to lower economic class, while 26% and 10% belongs to upper and middle class respectively. Patients with a family history of diabetes (41%) had good knowledge of diabetes when compared to patients with no family history of diabetes (58.99%). Conclusion: The increase in duration of diabetes also showed an increased awareness of the disease in our study groups. Imparting regular disease education to the patients will result in better awareness about the disease and encourages patients to follow better self care management and reduces the burden experienced by the patients.
Keywords: Diabetes; Diabetes Knowledge; Diabetes education; Health education; International Diabetic Federation